PENGARUH PENGGUNAAN VIDEO PEMBELAJARAN TERHADAP KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA KELAS IV PADA MATERI FOTOSINTESIS - Rini Marlina; Regina Lichteria Panjaitan; Atep Sujana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
High-order thinking skills (HOTS) are important skills that students must have to face the challenges of the 21st century. However, in reality, many elementary school students still have low HOTS skills, one of which is caused by the use of conventional learning media. This study aims to determine the effect of using learning videos on the high-order thinking skills of fourth-grade students on photosynthesis material. The method used in this study was a quasi-experimental design with a non-equivalent control group design. The sample in this study consisted of fourth-grade students in two elementary schools, namely fourth-grade Karanglayung as the control class (28 students) and fourth-grade SDN Gudang II as the experimental class (32 students). The instrument used was a high-order thinking ability test given before and after treatment. The results showed that the average pretest score of the control class was 46.71, while the experimental class was 56.91. After treatment, the average posttest score of the control class increased to 65.11, while the experimental class reached 82.50. Improvements in student abilities were seen in both groups, but the experimental class experienced a more significant increase, with an average n-gain score reaching 60% compared to 35% in the control class. Thus, it can be concluded that the use of learning videos has a positive effect on improving students' higher-order thinking skills in photosynthesis material.